2007
DOI: 10.1088/1748-6041/2/1/s06
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evaluation of whey protein-based biofilms as scaffolds for cutaneous cell cultures and biomedical applications

Abstract: This study evaluated the toxicity, biodegradability and immunogenicity of newly developed whey protein-based biofilms for possible use as biomaterials for medical applications. Biofilms were prepared using (A) a whey protein isolate plasticized with either diethylene glycol (DEG) or glycerol (GLY), and (B) beta-lactoglobulin (betaLGA) plasticized with DEG. The biofilms were implanted subcutaneously into Balb/c mice. Analyses were performed at various time points. At 15, 30 and 60 days post-implantation, no nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…After incubation, WPI/gelatin hydrogel showed significantly higher porosity and surface area than material before soaking in SBF, indicating degradation process of polymer matrix. Rouabhia, Gilbert, Wang, & Subirade () showed that WPI‐based films underwent almost complete degradation within 60 days after subcutaneous implantation into Balb/c mice. Because of different resorption time of individual components (WPI, gelatin, CaP phase), resulting composite hydrogels may show multistep degradation process in vivo.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After incubation, WPI/gelatin hydrogel showed significantly higher porosity and surface area than material before soaking in SBF, indicating degradation process of polymer matrix. Rouabhia, Gilbert, Wang, & Subirade () showed that WPI‐based films underwent almost complete degradation within 60 days after subcutaneous implantation into Balb/c mice. Because of different resorption time of individual components (WPI, gelatin, CaP phase), resulting composite hydrogels may show multistep degradation process in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Resulting films have been shown to support attachment and growth of normal human keratinocytes and fibroblasts isolated from skin. Furthermore, subcutaneous implantation of the films into Balb/c mice revealed that materials were not toxic and immunogenic as well as did not provoke fibrous encapsulation (Rouabhia et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Protein‐based biodegradable polymers are being widely used in biomedical applications since they exhibit superior biocompatibility especially those that present similarity to the extracellular matrix components . Such biopolymers can be classified as animal‐sourced protein‐based (e.g., casein, whey, albumin, keratin, collagen, and fibrin) and plant‐sourced protein‐based (e.g., wheat, soy, yeast, starch, and zein) biodegradable polymers. Compared to other plant‐based proteins, zein has significant and unique properties.…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that the protein containing PCL is not only non-toxic to the L929 cells, but may also enhance the cell proliferation. This further augments the recent in vivo finding of non-toxicity or immunogenicity of the diethylene glycerol plasticized whey protein and ␤-lactoglobulin biofilms [39]. However, to further verify these findings, the biomaterials were tested with the primary human keratinocytes.…”
Section: Cytotoxicity and Cell Proliferationmentioning
confidence: 53%